Self-administered EMDR therapy: potential solution for expanding the availability of psychotherapy for PTSD or unregulated recipe for disaster?. Issue 6 (2nd October 2020) - Waterman, Lauren Z.; Cooper, Maxwell
Abstract : Background: Post-traumatic stress disorder (PTSD) carries a high disease burden worldwide, yet significant barriers exist to providing and accessing treatment for PTSD, particularly in refugee populations and in low- and middle-income countries. There is emerging evidence that self-administered psychological therapies, such as those accessed via online and mobile applications, are efficacious for many mental illnesses and increase access to treatment. Online and mobile applications offering self-help tools for eye movement desensitisation reprocessing (EMDR) therapy, an internationally recommended treatment for PTSD, are already widely distributed to the public. Aims: To present a commentary evaluating the potential benefits and risks of self-administered EMDR therapy: first, by conducting a search for existing peer-reviewed evidence relating to self-administered EMDR therapy; second, by presenting existing evidence for other self-help psychotherapies and evaluating what additional insight this could provide into the potential efficacy, safety, tolerability and accessibility of self-administered EMDR therapy; and, third, by describing the conflicting views of EMDR experts on the topic. Method: A search was conducted for articles related to internet, mobile, book or computerised self-help EMDR therapy. The following databases were searched systematically: Medline, PsycInfo, EMBASE, AMED, CINAHL, Psychology and Behavioural Sciences, Cochrane Database and the EMDR Library. Results: Only one small primary research study was found relating to self-administered EMDR therapy. The results indicated significantly reduced symptoms of PTSD, depression, anxiety, distress and disability between pre-treatment and 3 month follow-up. No serious adverse events were reported. However, substantial methodological issues were discovered. Conclusions: There is evidence that self-administered psychotherapies, in general, can be safe, effective and highly accessible. However, controversies persist regarding the safety and potential efficacy of self-administered EMDR therapy, and more robust research is needed. It is vital that methods are found to improve worldwide access to effective PTSD treatment, particularly given the current scale of migration to flee civil unrest.